2022
DOI: 10.3390/jcm11133899
|View full text |Cite
|
Sign up to set email alerts
|

How Old Is Old? An Age-Stratified Analysis of Elderly Liver Donors above 65

Abstract: In liver transplantation, older donor age is a well-known risk factor for dismal outcomes, especially due to the high susceptibility of older grafts to ischemia-reperfusion injury. However, whether the factors correlating with impaired graft and patient survival following the transplantation of older grafts follow a linear trend among elderly donors remains elusive. In this study, liver transplantations between January 2006 and May 2018 were analyzed retrospectively. Ninety-two recipients of grafts from donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…According to our experience, we agree with the IFSO on evaluating patients suffering from NAFLD for TIPS implantation and consecutive SG. However, in Germany, we are facing severe organ scarcity and would not be able to facilitate LT for many cases after BS in due time ( 43 ). These patients typically present with a low MELD score with a very long waiting time on the waiting list.…”
Section: Discussionmentioning
confidence: 99%
“…According to our experience, we agree with the IFSO on evaluating patients suffering from NAFLD for TIPS implantation and consecutive SG. However, in Germany, we are facing severe organ scarcity and would not be able to facilitate LT for many cases after BS in due time ( 43 ). These patients typically present with a low MELD score with a very long waiting time on the waiting list.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies on donor age and graft loss in liver transplantation have seldomly studied PNF as an etiology. In a recent study by Houben et al [26] the authors stratified liver transplant donors into two groups, (65-69 years and ≥ 70 years) and found no statistical difference for rates of PNF between the groups. Additionally, that study found that one-year patient survival was not statistically different for donors <65 years and donors of 65-69 years (77.1% vs. 78.5%).…”
Section: Primary Graft Nonfunction (Pnf)mentioning
confidence: 97%
“…MP has shown substantial benefits compared to the conventionally used technique of static cold storage (SCS), especially considering the ever-growing dependence on organs with a higher susceptibility to IRI. These livers from extended criteria donors (ECD) usually combine multiple risk factors such as elevated donor age [8], steatosis (macrosteatosis > 30%, mixed steatosis > 60%), or prolonged cold ischemia time (CIT). In addition to maintaining organ viability, continuous oxygenated perfusion replenishes mitochondrial adenosine triphosphate (ATP) stores [9] and protects the organ by eliminating acidotic waste products.…”
Section: Mp Of Liver Grafts 21 Basic Concepts and Clinical Implicationsmentioning
confidence: 99%